1992
DOI: 10.1193/1.1585672
|View full text |Cite
|
Sign up to set email alerts
|

Improving Measures to Reduce Earthquake Casualties

Abstract: Current earthquake casualty reduction measures are examined and recommendations made for needed changes. Key new approaches are outlined and a new framework for understanding casualty reduction measures presented. The framework considers both issues of demand for medical services and supply within primary, secondary and tertiary prevention aspects of each. It is used to assess current measures against recent empirical data and to suggest changes that incorporate new data and methods. Issues include the managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Durkin et al 21 indicated that building codes and regulations, which have as their goal the prevention of structural collapse and the restraint of hazardous nonstructural elements, are the principal policy instruments for the primary prevention of injuries. Because earthquakes cannot be avoided, a better understanding of the structural characteristics of buildings, and their capability to withstand seismic forces, is essential in determin-ing relief needs and the appropriate public health response.…”
Section: Discussionmentioning
confidence: 99%
“…Durkin et al 21 indicated that building codes and regulations, which have as their goal the prevention of structural collapse and the restraint of hazardous nonstructural elements, are the principal policy instruments for the primary prevention of injuries. Because earthquakes cannot be avoided, a better understanding of the structural characteristics of buildings, and their capability to withstand seismic forces, is essential in determin-ing relief needs and the appropriate public health response.…”
Section: Discussionmentioning
confidence: 99%
“…In earthquakes of all magnitudes, there is generally enough time to react before peak motion (Lomnitz 1970;Armenian et al 1992;Roces et al 1992;Durkin and Thiel 1992). During North American earthquakes, one of the common reactions is to rapidly exit a building during shaking.…”
Section: Rationalmentioning
confidence: 96%
“…All three earthquakes representing light damage and high earthquake education were twentieth-century earthquakes from California (1989Loma Prieta, 1992Landers, and 1994. Researchers have noted that a significant number of minor injuries were likely treated but not reported (Durkin and Thiel 1992;McKevitt et al 1995;McArthur et al 2000). (2) Moderate damage is classified as primarily structural failures of moderate material (e.g., timber-frame) and/or low-rise buildings.…”
Section: Limitations In Model Approachmentioning
confidence: 99%
“…The second-and third-degree severity require specialized medical attention and hospitalization, however, unlike the second degree, the third one requires immediate rescue and treatment to avoid death. [58][59][60] We considered that 100% of the patients with third-degree injuries, for example, having punctured organs or crush syndrome with exposed wounds, plus 10% of patients with second-degree injuries, for example, having compound bone fractures, will require surgical treatment in operating rooms. We considered that patients arrive to the closest hospital during a period of 4 days after the earthquake in accordance to the evidence from previous earthquakes.…”
Section: Earthquake Casualty Modelingmentioning
confidence: 99%